Interactions Between Epilepsy and Plasticity - José J. Jarero-Basulto; Yadira Gasca-Martínez; Martha C. Rivera-Cervantes; Mónica E. Ureña-Guerrero; Alfredo I. Feria-Velasco; Carlos Beas-Zarate (MDPI AG, 2018)
Undoubtedly, one of the most interesting topics in the field of neuroscience is the ability of the central nervous system to respond to different stimuli (normal or pathological) by modifying its structure and function, either transiently or permanently, by generating neural cells and new connections in a process known as neuroplasticity. According to the large amount of evidence reported in the literature, many stimuli, such as environmental pressures, changes in the internal dynamic steady state of the organism and even injuries or illnesses (e.g., epilepsy) may induce neuroplasticity. Epilepsy and neuroplasticity seem to be closely related, as the two processes could positively affect one another. Thus, in this review, we analysed some neuroplastic changes triggered in the hippocampus in response to seizure-induced neuronal damage and how these changes could lead to the establishment of temporal lobe epilepsy, the most common type of focal human epilepsy.